STRATEGI INTEGRATED MARKETING COMMUNICATION PT GO-JEK DALAM LAYANAN JASA GO-FOOD - RESTY MUSTIKA PRATIWI; IIS ZILFAH ADNAN; Mega Agustina Putu Sanusi (Prodi Ilmu Komunikasi Universitas Putera Batam, 2022)
This research is motivated by the achievements of PT Go-Jek in marketing Go-Food services in the past two years. The achievements are allegedly caused by the implementation of the Integrated Marketing Communication (IMC) strategy through the activities of advertising, personal selling, sales promotion, marketing sponsorship, public relations, and point of purchase communication. These activities involve the use of marketing tools, which include digital tools, tool components, and digital access, as well as aspects of the company's human resources effectively. The purpose of this research is to find out and analyze the steps of the Integrated Marketing Communication strategy of PT Go-Jek in the Go-Food service in Garut. The results of the study concluded, that: 1) PT Go-Jek's Human Resources are sufficiently adequate in terms of competence to properly implement all aspects of the IMC; understanding of the use of digital devices (digital tools) is quite good; understanding the use of tool components is good; understanding the use of digital access is also quite good; 2) Advertising material or messages of Go-Food services by PT Go-Jek are good, both through online and offline media; 3) The concept of direct offers through personal selling on Go-Food services by PT Go-Jek is good, both through online and offline media; 4) Direct incentives/bonuses through sales promotion by PT Go-Jek have been implemented well in attracting consumers; 5) Through marketing sponsorship in Go-Food services, PT Go-Jek's sponsor activities in an event are quite good; 6) Activities to establish relationships and social communication through public relations, such as updating the appearance of the Go-Jek application are quite well implemented; and 7) The use of several advertising tools and media, both in the PT Go-Jek office and in public places through point of purchase communication, is also carried out quite well. Keywords: Integrated Marketing Communication, Digital Marketing Tools, Go-Jek and Go-Food Services